(untitled) (Literatures of the World: Poetics, Mentality and Spirituality, 2018)
The article investigates the development of upbringing novel in the Ukrainian literature of the beginning of the 20th century. It clarifies the characteristics of the genre modifications. On the material of the dilogy written by O. Kopylenko "Very Good" and "Tenth-graders", the research analyzes problem-thematic components and style dominants, which determine the content of the ideological project of education.